Cryptocurrency: A Mine of Controversies - Molling, Graziela; Klein, Amarolinda; Hoppen, Norberto; Rosa, Rafael Dalla (Journal of Information Systems and Technology Management, 2020)
Cryptocurrency is attracting the attention of many disciplines. Based on a systematic literature review, the state of art of academic research on cryptocurrency was investigated, demonstrating its complexity and the lack of consensus about several issues, as its definition, its operation without a financial institution, the impacts on economy and its future developments. Considering these issues, Actor-Network Theory was selected as a theory that can provide methods, such as controversy mapping, to understand this complex subject. The article analyzes this scenario, presenting a set of research topics that can be considered to study controversies related to cryptocurrency.